2009 First International Conference on Ubiquitous and Future Networks 2009
DOI: 10.1109/icufn.2009.5174278
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of backbone-assisted end-to-end transmissions in WSNs

Abstract: Many anticipated deployment scenarios, in particular military, healthcare, and disaster-recovery applications, of Wireless Sensor Networks (WSNs) require reliable source to sink communication. Since transmission range of sensors is quite limited, to achieve higher end-to-end transmission reliability, WSNs generally employ intermediate backbone links (wired or wireless) that can deliver packets at larger distances. In this paper, we evaluate the reliability of backbone-assisted routing and dissemination in WSNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Tufail et al [72] have also demonstrated mathematically that backbone-assisted routing gives noticeably better reliability in comparison to traditional all wireless ad hoc routing. Thus a WSNA with wired Actuators serving as backbone, communicating wirelessly with the nodes, is likely to offer better reliability viz a viz the traditional all wireless adhoc routing.…”
Section: Resultsmentioning
confidence: 99%
“…Tufail et al [72] have also demonstrated mathematically that backbone-assisted routing gives noticeably better reliability in comparison to traditional all wireless ad hoc routing. Thus a WSNA with wired Actuators serving as backbone, communicating wirelessly with the nodes, is likely to offer better reliability viz a viz the traditional all wireless adhoc routing.…”
Section: Resultsmentioning
confidence: 99%